Ancient Trade Corridor Tamralipti and Bengal’s Glory (200 BCE–700 CE) (KEMANUSIAAN The Asian Journal of Humanities, 2022)
Tamralipti was a port of ancient Bengal used as a corridor for international trade and it played a critical role in bringing fame and glory to Bengal. This study investigates the role of this port that contributed towards the socioeconomic and sociocultural supremacy from 200 BCE to 700 CE. Archaeological remains proved the trade contacts of this port with several domestic and foreign geographical entities such as Southeast Asia, China and Rome. The sequential dominance and fame of this port aided to enrich the society and structure the trade-related social classes in ancient Bengal until the deterioration and decline of this port after the seventh century CE. The study employs a qualitative method using historical research that focuses on ancient texts, archaeological findings and reports as primary sources. The information gathered from field visits and published literature is also consulted through archival and library research. The result of this study reveals the leading role of Tamralipti as a corridor that signifies the image of Bengal concerning political, economic and sociocultural aspects.